Electrochemical Characterization of Iron (III) Doped Zeolite-Graphite Composite Modified Glassy Carbon Electrode and Its Application for AdsASSWV Determination of Uric Acid in Human Urine - Meareg Amare (International Journal of Analytical Chemistry)
Iron (III) doped zeolite/graphite composite modified glassy carbon electrode was prepared for determination of uric acid in human urine samples. Electrochemical impedance spectroscopic and cyclic voltammetric results confirmed surface modification of the surface of glassy carbon electrodes. Appearance of oxidative peak current with an over threefold enhancement at significantly reduced overpotential for uric acid at the composite modified electrode relative to the unmodified and even graphite modified electrode confirmed the electrocatalytic property of the composite towards electrochemical oxidation of uric acid. Under optimized method and solution parameters, linear dependence of peak current on uric acid concentration in a wide range of 1-120 μM, low detection limit value (0.06 μM), replicate results with low RSD, and excellent recovery results (96.61-103.45%) validated the developed adsorptive anodic stripping square wave voltammetric (AdsASSWV) method for determination of uric acid even in aqueous human urine samples. Finally, the developed composite modified electrode was used for determination of uric acid content in human urine samples collected from three young male volunteers. While the uric acid level in the urine samples from two of the studied volunteers was within the normal range, of the third was under the normal range.